Rheological Method for Alpha Test Evaluation of Developing Superplasticizers’ Performance: Channel Flow Test - Jae Hong Kim; Jin Hyun Lee; Tae Yong Shin; Jin Young Yoon (Advances in Materials Science and Engineering)
Advance in high-range water-reducing admixture revolutionizes the workability and constructability of conventional vibrated concrete as well as self-consolidating concrete. Its need from construction fields has increased, and consequently a variety of new-type polycarboxylates, base polymers for the admixture, are being formulated in these days. Synthesizing new polymers needs a quick, but reliable, test to evaluate its performance on concrete. The test is also asked for selecting the best applicable brand of them before a test concrete will be mixed. This paper proposes a “channel flow test” and its usage for the purpose. The proposed procedure for the test includes the mix proportion of a test mortar, the test method, and rheological interpretation of the test results.